Melittin Treatment for Biofilm of MRSA (Methicillin Resistant Staphylococcus aureus) - Dwi Marlina (Jurnal Ilmu Kedokteran dan Kesehatan, 2019)
According to the Centers for Disease Control and Prevention (CDC) there were estimated to be 94,360 MRSA invasive infections in the US with approximately18,650 deaths annually since 2005.Other organizations estimate the true numbers to be over one million infected in the US with MRSA and over 100,000 deaths from 2005-2010.These infections attack all ages, from the elderly to the young, mainly because their immune system is suppressed.  In acute care hospitals, MRSA colonization is a common cause of nosocomial infection and increased hospital costs (Huh, Kim, &Chae, 2012).  MRSA universally attach to surfaces and produce extracellular polysaccharides, resulting in the formation of abiofilm. Biofilms pose a serious problem for public health because of the increased resistance of biofilm-associated organisms to antimicrobial agents and the potential for these organisms to cause infections in patients with indwelling medical devices.An appreciation of the role of biofilms in infection should enhance the clinical decision-making process.Currently, biofilm is considered as a major mediator of infection with an estimated 80% incidence of infection associated with the formation of biofilms.  Biofilm resistance is usually multifactorial, which makes it difficult to eradicate biofilms.  Therefore, this study will focus on creatingMethicilin ResistantStaphylococcus aureusbiofilms in culture and on testing the effects on that biofilm of the antibacterial peptide: Melittin.Method:This study is an experiment and the strain of Methicillin Resistant Staphylococcus aureus(MRSA) was WBG 8287 which was donated by France O Brien who is from the medical research facility of royal Perth hospital.Result:The biofilm formation produces large amounts of non-cellular material with very few visible cells.  The thickness of film shows that MRSA produced biofilm well.  Melittin able to treat MRSAwith 60 minutes having stable colorConclusion:The resultsshowed that the procedures used were capable of inducing this MRSA strain to form a biofilm and melittin able to treat MRSA.Suggestion:However, it is still not a perfect trial. Therefore, for the foreseeable future will be carried out the modified experiment and the experiment should be done with the variation of treatment and increasing the time of treatment.  It aims to get the best results in the healing process of the disease which is caused by MRSA.